Biofilms possibly harbor occult SARS-CoV-2 may explain lung cavity, re-positive and long-term positive results - He, Daqian; Fu, Chaojiang; Ning, Mingjie; Hu, Xianglin; Li, Shanshan; Chen, Ying (Frontiers in Cellular and Infection Microbiology, 2022)
During the COVID-19 pandemic, there have been an increasing number of COVID-19 patients with cavitary or cystic lung lesions, re-positive or long-term positive nucleic acid tests, but the mechanism is still unclear. Lung cavities may appear at long time interval from initial onset of coronavirus infection, generally during the absorption phase of the disease. The main histopathological characteristic is diffuse alveolar damage and may have more severe symptoms after initial recovery from COVID-19 and an increased mortality rate. There are many possible etiologies of pulmonary cavities in COVID-19 patients and we hypothesize that occult SARS-CoV-2, in the form of biofilm, is harbored in the airway lacuna with other pathogenic microorganisms, which may be the cause of pulmonary cavities and repeated and long-term positive nucleic acid tests.